Isolasi dan Identifikasi Ras Pyricularia grisea pada Tanaman Padi Asal Manokwari dan Manokwari Selatan, Papua Barat - Santoso, Santoso; Sipi, Surianto; Subiadi, Subiadi; Nasution, Anggiani (Jurnal Penelitian Pertanian Tanaman Pangan, 2019)
Manokwari and South Manokwari Regency is one of the rice development areas in West Papua. Planting of lowland rice in Manokwari and South Manokwari always infect by blast disease. The use of resistant varieties is a major component in controlling blast disease and is the most effective, economical, and easy way for farmers. The use of blast resistant varieties is limited by space and time; in this case the use of resistant varieties must be adjusted to the composition of the P. grisea races in the area. Until now there has been no isolation and identification of P. grisea races that developed in Manokwari and South Manokwari Regency. The study aimed to identify the composition of P. grisea races in Manokwari and South Manokwari areas. The research was carried out in the laboratory and greenhouse of the Muara Bogor Experimental. Isolation and identification of race P. grisea was carried out in 2017. The results showed that the results of P. grisea isolation using monoconidia obtained 34 isolates, which were obtained from the Prafi, Masni, Oransbari and Sidey Districts. Race identification of P. grisea was obtained by 9 race groups namely race 211, 213, 241, 251, 253, 313, 333, 353 and race 373, which were dominated by race 333 as much as 41.18% and race 373 by 33.35%. The P. grisea races obtained are races that have a high virulence level.